Chronic Obstructive Pulmonary Disease: an Overview - Budianti, Titiek (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Chronic Obstructive Pulmonary Disease (COPD) is a progressive respiratory disorder and a leading cause of morbidity and mortality worldwide. Despite advances in research, COPD continues to impose a significant global health and economic burden. This article is a narrative review of current literature focusing on the definition, epidemiology, etiology, pathophysiology, clinical manifestations, management, and complications of COPD. Relevant studies, international guidelines, and recent updates were analyzed to provide a comprehensive understanding of the disease. COPD prevalence is increasing globally, especially in developing countries, with smoking, air pollution, occupational exposures, and genetic susceptibility identified as major risk factors. Pathophysiological mechanisms include chronic inflammation, oxidative stress, and protease–antiprotease imbalance, leading to irreversible structural changes in the lungs. Clinically, patients present with chronic cough, sputum production, and progressive dyspnea. Management involves risk factor control, pharmacological treatment, pulmonary rehabilitation, and multidisciplinary care. Complications such as recurrent exacerbations, pulmonary hypertension, and chronic respiratory failure further worsen prognosis. In conclusion, a comprehensive understanding of COPD from multiple perspectives is crucial for optimizing prevention, diagnosis, and treatment. This review emphasizes the need for early detection, integrated therapeutic approaches, and ongoing research to reduce the global burden of COPD.